Histopathological Examination and Endoscopic Sinusectomy: Is It Possible? - Vertaldi, Sara; Anoldo, Pietro; Cantore, Grazia; Chini, Alessia; D'Amore, Anna; D'Armiento, Maria; Gennarelli, Nicola; Maione, Francesco; Manigrasso, Michele; Marello, Alessandra; Schettino, Pietro; Sorrentino, Carmen; et al. (Frontiers in Surgery, 2022)
Introduction: Although carcinomatous degeneration is a rare occurrence, some authors support the need for a histopathological examination after pilonidal cyst excision. Today, minimally invasive techniques are widely spread for the treatment of pilonidal sinus disease but opposed to standard procedures, these techniques could not allow to perform a histopathological examination because of the absence of a specimen. The aim of this two-institutions study is to evaluate whether histopathological examination of the pilonidal sinus excision material can be successfully performed after an endoscopic ablation of the cyst. Materials and methods: We identified all consecutive patients from January 2021 to September 2021 with diagnosis of pilonidal sinus disease who underwent Video Assisted Ablation of Pilonidal Sinus (VAAPS) followed by histopathological examination. Results: A total of 45 patients were included in the study. All patients were Caucasians and aged below 50 years. Nine of them underwent surgery due to recurrence of PSD. No evidence of malignancy was detected in the histopathological examination of the pilonidal sinus excision materials. Discussion: We were able to send pilonidal sinus material for a histopathological examination in all patients who underwent minimally invasive technique for the treatment of pilonidal sinus disease. No evidence of malignancy was found in any of the 45 samples. Our findings prove that minimally invasive ablation of pilonidal sinus does not preclude histopathological examination of the cysts and the possibility to diagnose malignant degeneration.